2014
DOI: 10.1016/j.bbamem.2014.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Ionomycin causes susceptibility to phospholipase A2 while temperature-induced increases in membrane fluidity fail: Possible involvement of actin fragmentation

Abstract: A diminution in the order of membrane lipids, which occurs during apoptosis, has been shown to correlate with increased membrane susceptibility to hydrolysis by secretory phospholipase A2. Studies with artificial membranes, however, have demonstrated that the relationship between membrane order and hydrolysis is more complex than suggested thus far by cell studies. To better resolve this relationship, this study focused on comparisons between increasing temperature and calcium ionophore as means of decreasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It has been shown that a decrease in temperature of growing bacteria causes incorporation of more unsaturated fatty acids in their membranes followed by remodeling and change in cell fluidity [14]. a dependence of cell membrane fluidity on surrounding temperature expressed by changes in membrane lipid composition has been reported in other studies [15,16]. Increased cell membrane fluidity with subsequent enhanced phagocytosis may explain the promoting engulfment of latex particles by PBMC incubated with hydrophobic statins [12].…”
Section: Discussionmentioning
confidence: 87%
“…It has been shown that a decrease in temperature of growing bacteria causes incorporation of more unsaturated fatty acids in their membranes followed by remodeling and change in cell fluidity [14]. a dependence of cell membrane fluidity on surrounding temperature expressed by changes in membrane lipid composition has been reported in other studies [15,16]. Increased cell membrane fluidity with subsequent enhanced phagocytosis may explain the promoting engulfment of latex particles by PBMC incubated with hydrophobic statins [12].…”
Section: Discussionmentioning
confidence: 87%
“…This ionophore disrupts cell-cell adhesion, cleaves E-Cadherin, modifies biochemical characteristics of lipids membrane ( i.e. fluidity and distribution) and enhances PS externalisation, which might interfere with our model of cell fusion 27 28 . Thus, the mammalian expression vector encoding for E-Cadherin fused to GFP (E-Cadherin-GFP) was introduced in primary human trophoblasts depleted or not of endogenous AnxA5 by siRNA transfection and rescued with either mCherry-AnxA5* or mCherry-AnxA5*-2Dmut ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…small unilamellar vesciles or planar supported lipid bilayers). Artificial membranes lack physiological processes that control biochemical properties of the membrane and observations performed with these models might differ from physiological conditions 27 . Interestingly, intracellular Ca 2+ concentration in subplasmalemma microdomains fits with the lowest concentration of Ca 2+ that have been described to promote AnxA5 binding to PS and 2D-network assembly 18 34 35 .…”
Section: Discussionmentioning
confidence: 99%